Infrastructure Development in Sub-Saharan Africa : A Scorecard - Calderon, Cesar; Cantu, Catalina; Chuhan-Pole, Punam (World Bank, Washington, DC, 2018)
Infrastructure is viewed as a crucial ingredient to foster growth and productivity. Amid the post -- global financial crisis slowdown, Sub-Saharan Africa is in dire need to continue the growth momentum it experienced during the period of the Africa Rising narrative. An emerging consensus in the empirical literature is that, under the right circumstances, an adequate supply of infrastructure can help foster growth in the region. This paper provides a scorecard on infrastructure development in Sub-Saharan Africa over the past decades along four sectors (telecommunications, electric power, transportation, and water and sanitation) and three dimensions (quantity, quality, and access). First, it documents the existence of a large gap in infrastructure in the region—although the magnitude of the gap depends on the sector, dimension, and country/group. Second, the potential growth benefits from closing the infrastructure gap are large. Third, the infrastructure financing needs are very large, and the public sector so far is unable to meet these needs. Other options that involve the private sector may be available for the region. Finally, there is room for improving the efficiency of public infrastructure spending (that is, the quality of public investment management systems and procurement methods), which, in turn, may increase the output multiplier of investment spending.